PERATURAN KEBIJAKAN PENDIDIKAN DI INDONESIA PADA MASA ORDE LAMA, ORDE BARU, REFORMASI, DAN KABINET KERJA - Sarfika Datumula (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2020)
The education system as we know it today is the result of educational developments that have grown in the history of our nation's experience. There have been some writings discussing the regulations of education policy in Indonesia from time to time, but this paper examines the comparison of education policies from the Old Order era to the implementation of education policies to the work cabinet period. Through a literature review, this paper aims to describe how education policy regulations in Indonesia were during the Old Order, New Order, Reform, and Work Cabinet Periods. The results of this study reveal as has been explained in the discussion, that during the New Order era education only took place in terms of quantity without being matched by quality developments. In this period, it is to create as many educated graduates as possible without producing quality teaching and educational outcomes. The curricula used at this time were the 1968 curriculum, the 1975 curriculum, the 1984 curriculum, and the 1994 curriculum. However, education in the next period during the New Order period was not said to be fully successful, so in the next period of the reform period, improvements were needed, both in the field of curriculum. as well as in terms of the teaching staff. The curricula used in this reform era are the Competency-Based Curriculum (KBK) and the Education Unit Level Curriculum (KTSP), and K13.